2019
DOI: 10.1017/wet.2019.129
|View full text |Cite
|
Sign up to set email alerts
|

Relative activity comparison of aminocyclopyrachlor to pyridine carboxylic acid herbicides

Abstract: The pyridine carboxylic acid (PCA) herbicide family can exhibit differential activity within and among plant species, despite molecular resemblances. Aminocyclopyrachlor (AMCP), a pyrimidine carboxylic acid, is a recently discovered compound with similar use patterns to those of the PCA family; however, relative activity among PCAs and AMCP is not well understood. Therefore, the objective of this study was to quantify relative activity among aminopyralid, picloram, clopyralid, triclopyr, and AMCP in canola, sq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…Other chloro-substituted pyrazine rings evaluated in our studies (compounds 3 – 8 ) did not display any auxin herbicidal activity, and this is consistent with past research of compounds 4 , 6 , and 7 in pea (Pisum sativum) . In fact, the researchers concluded that pyrimidine and pyrazine rings are not capable of being auxin mimic herbicides, which has since been disproven by the commercial pyrimidine auxin mimic herbicide aminocyclopyrachlor and our pyrazine compound 9 . , …”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Other chloro-substituted pyrazine rings evaluated in our studies (compounds 3 – 8 ) did not display any auxin herbicidal activity, and this is consistent with past research of compounds 4 , 6 , and 7 in pea (Pisum sativum) . In fact, the researchers concluded that pyrimidine and pyrazine rings are not capable of being auxin mimic herbicides, which has since been disproven by the commercial pyrimidine auxin mimic herbicide aminocyclopyrachlor and our pyrazine compound 9 . , …”
Section: Resultssupporting
confidence: 91%
“…36 In fact, the researchers concluded that pyrimidine and pyrazine rings are not capable of being auxin mimic herbicides, which has since been disproven by the commercial pyrimidine auxin mimic herbicide aminocyclopyrachlor and our pyrazine compound 9. 36,37 The exact herbicidal site of action targeted by compounds 3, 5, 14, 15, 24, and 25, which provides such distinct chlorosis, stunting, and eventual necrosis on yellow nutsedge but to a much lesser extent on other crops and weeds, is currently unknown (Tables 1−5). From a global perspective, yellow nutsedge is one of the world's worst weeds, and as a perennial is very difficult to control because herbicides must travel to the underground tubers and accumulate in toxic amounts to prevent regrowth.…”
Section: Acs Agriculturalmentioning
confidence: 99%
“…Aminocyclopyrachlor and aminopyralid are primarily noncrop herbicides that can be used in seasonally dry wetlands and to the water's edge in natural areas (Anonymous 2017(Anonymous , 2018a. Aminopyralid is selective among dicots (Mikkelson and Lym 2013), while aminocyclopyrachlor is generally less selective but is effective in controlling resilient woody species (Enloe et al 2015;Sperry et al 2020). Recent research has demonstrated that both herbicides are highly effective on S. terebinthifolia when applied as individual plant treatments (e.g., cut stump and stem injection) (Bell 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Given that picloram is not registered for use in Florida because of environmental concerns and that aminopyralid has been a standard component of pasture weed management in Florida since its introduction in 2004, it is important to compare aminopyralid's efficacy on Nuttall's thistle with other commonly used pasture herbicides such as 2,4‐D and dicamba. Additionally, it is important to investigate the efficacy of aminopyralid and other pyridine carboxylic acid herbicides on individual weed species, as previous research has indicated that their activity can be species‐specific rather than uniform across weeds from the same family or genera (Enloe et al., 2007; Sperry, Dias, Prince, Ferrell, & Sellers, 2020). Therefore, the objectives of this study were: (a) to compare the effectiveness of aminopyralid with 2,4‐D and dicamba applied at two application timing (rosettes vs. bolting), and (b) to determine the most effective aminopyralid rate via field dose–response studies.…”
Section: Introductionmentioning
confidence: 99%